Endoscopic Evaluation of Dyspeptic Patients (Journal of Shaheed Suhrawardy Medical College, 2021)
Background: Dyspepsia is a common gastrointestinal problems affecting all age groups & social classes.Objectives: The purpose of the study was to determine the endoscopic findings of dyspeptic patients & to observe the demographic characteristics (age, sex, residence, education, socioeconomic condition) of the patients presented with dyspepsia.Methodology: This was a cross-sectional study conducted at Department of Medicine, Rangpur Medical College Hospital, Rangpur over a period of 1 year from 1st June 2010 to 31st May 2011. 150 dyspeptic patients of 18 or > 18 years old irrespective of sexes and suffering from one or more of the five symptoms (flatulence, food intolerance, epigastric pain, heartburn and aerophagia) for at least 6 months duration were recruited for the study from outpatient and inpatient department who were met the inclusion & exclusion criteria. Data were collected by using a structured questionnaire after taking written consent & upper GI Endocopy were done following meticulous history & through physical examination.Result: Over one-third (36%) of the patients were below 30 years, 17% between 30 – 40 years old, predominantly were rural residents, having primary to secondary level of education with monthly income below Taka 10000. Males to females ratio were 2:1. More than half (50.6%) of the patients was smoker, 32.7% had habit of taking tea, 10% were tobacco chewing and rest 6.7% used to take spicy meal.. Epigastric discomfort, flatulence and heartburn were the common complaints in both male and females but vomiting were proportionately higher in male dyspeptics compared to the female dyspeptics. Common associated symptoms like constipation and weight loss were equally in both sexes. Upper GI endoscopy revealed 17.3% of male and 11.5% of female with abnormal findings.Others abnormal findings included gastric ulcer, gastritis and duodenal ulcers (17.6 vs. 33.3%; 23.6 vs. 50% and 17.6 vs. 16.7% in male and female respectively). Majority (nearly 90% in either sex) of patients does not show any lesions on endoscopic examination and hence can be considered as non-ulcer dyspepsia.Conclusion: The study concludes that majority of patients with complaints of dyspepsia have no lesion on the gastric or duodenal mucosa and can be considered non-ulcer dyspepsia. The study findings also suggest that dyspepsia is a disease of young and early middle aged people with males being more likely to develop the disease than the females. However, large-scale community survey is recommended for further evaluation of dyspepsia.J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 9-14